INTERACTION OF THE ACCOUNTING CHAMBER OF UKRAINE WITH OTHER SUBJECTS OF STATE FINANCIAL CONTROL - Maletska , O.I. (The actual problems of regional economy development, 2021)
Interaction of the Accounting Chamber of Ukraine with other subjects of state financial control. Given the relevance of the chosen research topic, the aim of the article is further theoretical study of such an external control body as the Accounting Chamber of Ukraine, clarification of the interaction of the above control body with other subjects of state financial control: Verkhovna Rada of Ukraine, Cabinet of Ministers, President of Ukraine. In the process of writing the article, inductive, deductive methods was used, which were used to study the functions of the Accounting Chamber. The graphic method was used to clearly reflect the construction and formation of the powers of the Accounting Chamber in accordance with the law. An abstract-logical method is used for theoretical generalizations and formation of conclusions. It is established that the state financial control, which is carried out by the Accounting Chamber of Ukraine in the form of audits, inspections, is an important function of managing the financial system, aimed at preventing and preventing financial and economic violations in the use of budget funds. In this regard, the main purpose of public financial control is to ensure compliance with the principles of legality, expediency and effectiveness of administrative and executive actions for the management of public finances and property of the state, their preservation and increase to fully perform state functions. It is noted that the object of state financial control is monetary relations that arise in the formation process and use of public finances and property of the state, as well as other economic entities. They are legal entities that, on behalf of the state (in accordance with the regulated legal norms), monitor other forms of control over the activities of economic entities in terms of compliance with the established restrictive parameters for the circulation of financial resources. As a result of the study of theoretical and practical issues of the functioning of the public financial system with the Accounting Chamber of Ukraine, we believe that it is necessary to clarify the principles of interaction of the Chamber with other financial control bodies. The theoretical and practical value of the study consist in identification of the interaction level of the Accounting Chamber of Ukraine with other subjects of public financial control.